PARAMETRIC MODELING OF MULTIFUNCTIONAL BUILDINGS IN THE BIM SYSTEM - Shovkat Ikramov; Zafar Matniyazov; Lobar Rasul-Zade; Timur Safiev; Xurshida Avloqulova (Scholar Express Journal, 2024)
This article analyzes the design and architectural features of multifunctional buildings, particularly exhibition centers, and explores the integration of parametric modeling within the Building Information Modeling (BIM) system. The study focuses on the evolution of exhibition spaces, their key functions, and the role of advanced technologies in improving design efficiency. Special attention is paid to the significance of physical and functional requirements for exhibition buildings and how parametric modeling in BIM can address these needs. The article highlights the advantages of using BIM for multifunctional exhibition centers, emphasizing its impact on flexibility, efficiency, and sustainability
Keywords: Exhibition buildings; BIM; parametric modeling